(untitled) (INNOVATIVE ECONOMY, 2019)
Okhota V.I. MODERN COMPETITIVE STRATEGIES ON INCREASING DOMESTIC TOURIST FLOWS Purpose. The research is aimed at complex systematization of competitive strategies to increase domestic tourism flows. Methodology of research. The research process is carried out using a systematic approach, which allowed systematizing the main scientific approaches to competitive strategies in relation to the increase of internal tourist flows; a complex method of research, by which a set of competitive strategies in this direction is determined. Findings. The main scientific approaches to competitive strategies concerning the increase of domestic tourist flows are identified and characterized in the article. A complex of competitive strategies is formulated on the basis of these approaches, which are most effective at the present stage of development in relation to the increase of internal tourist flows. The mentioned set of strategies is represented by: adapted development strategies in terms of: strategies related to concentrated, integrated, diversified growth; innovative competitive strategies ahead of development; competitive strategies of functioning in the domestic tourism market in view of the consistency of the combination of competitive advantages with the expectations of client groups; promising breakthrough strategies based on public and private partnerships, scientific and innovative components of tourism development. Originality. The scientific novelty of this study is that for the first time in the scientific space, the use and development of innovative competitive strategies of advanced development (a group of strategies within the framework of development strategies), which can be used in the current conditions of the tourism industry, are proposed and substantiated, and the characteristics of which correspond to the needs of this sphere in the innovation growth. Practical value. The complex of competitive strategies presented in the study allows to broaden the theoretical basis for the study of this issue, in practical terms this complex can be used as a visual format for improvement of strategic management at the level of the subjects of the industry, aimed at increasing the competitive position in the domestic market, etc. Key words: domestic tourism flows, competitive strategy, development strategy, tourism industry, promotion, innovation strategy, forward development, breakthrough strategies.